X-ray Spectroscopic Studies of a Solid-Density Germanium Plasma Created by a Free Electron Laser - Gabriel Pérez-Callejo; Sam M. Vinko; Shenyuan Ren; Ryan Royle; Oliver Humphries; Thomas R. Preston; Bruce A. Hammel; Hyun-Kyung Chung; Tomas Burian; Vojtěch Vozda; Ming-Fu Lin; Tim Brandt van Driel; et al. (Applied Sciences, 2020)
The generation of solid-density plasmas in a controlled manner using an X-ray free electron laser (XFEL) has opened up the possibility of diagnosing the atomic properties of hot, strongly coupled systems in novel ways. Previous work has concentrated on K-shell emission spectroscopy of low Z (<= 14) elements. Here, we extend these studies to the mid-Z(=32) element Germanium, where the XFEL creates copious L-shell holes, and the plasma conditions are interrogated by recording of the associated L-shell X-ray emission spectra. Given the desirability of generating as uniform a plasma as possible, we present here a study of the effects of the FEL photon energy on the temperatures and electron densities created, and their uniformity in the FEL beam propagation direction. We show that good uniformity can be achieved by tuning the photon energy of the XFEL such that it does not overlap significantly with L-shell to M-shell bound-bound transitions, and lies below the L-edges of the ions formed during the heating process. Reasonable agreement between experiment and simulations is found for the emitted X-ray spectra, demonstrating that for these higher Z elements, the selection of appropriate XFEL parameters is important for achieving uniformity in the plasma conditions.